Pengaruh Beban Kerja dan Lingkungan Kerja Terhadap Turnover Intention pada Kurir X Rantelemo - Christia Hasteti; Olivia Devi Y. Pompeng; Adriana Madya Marampa (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study was conducted with the aim of determining the influence of workload and work environment on turnover intention among employees at X Rantelemo. Turnover intention is an important indicator in human resource management because high employee intention to leave can negatively impact company productivity, operational stability, and recruitment and training costs. Therefore, factors that influence turnover intention, such as excessive workload and work environment conditions, are important to be studied in depth. The research method used is a quantitative method with data collection through distributing questionnaires to couriers working at X Rantelemo. The collected data were then analyzed using the SPSS version 23 application with a series of statistical tests, including classical assumption tests, research instrument tests, multiple linear regression tests, hypothesis tests, determination coefficient tests, correlation coefficient tests, and simultaneous tests. The results of data processing indicate that simultaneously workload (X1) and work environment (X2) do not have a significant effect on turnover intention (Y). This is indicated by the calculated F value of 6.558 which is greater than Ftable 3.33, with a significance value of 0.400 > 0.05. Furthermore, partial tests showed that the workload variable had no significant effect, as indicated by a t-value of -1.699 < t-table 2.04841 and a significance value of 0.100 > 0.05, thus rejecting the second hypothesis. Therefore, it can be concluded that in the context of this study, workload and work environment are not the dominant factors influencing employee turnover intention. This opens up the possibility that other factors, such as compensation, job satisfaction, leadership style, and career opportunities, have a greater influence on employees' desire to leave the company.